The Role of Constitutional Law in Shaping A Democratic Rule of Law in Indonesia - Cibu, Andi (Golden Ratio of Law and Social Policy Review, 2024)
The history of the Indonesian government clearly stems from its legal history, especially Constitutional Law, which plays an important role in the structure of government. This research aims to find out the history of Constitutional Law and the role it plays in the formation of the government system that has developed to date. To achieve this goal, the research method used in this research is normative juridical, or library research. Constitutional Law has many important roles, such as resolving disputes between the government and citizens, mediating or mediating to resolve problems between the government and society, and teaching the Indonesian government to adapt to new challenges and opportunities.